2005
DOI: 10.1097/01213011-200512000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cytochrome P450 3A5 enzyme for blood pressure regulation in the general Caucasian population

Abstract: Cytochrome P450 3A (CYP3A) enzymes are important for drug metabolism in gut and liver. The CYP3A5 isoenzyme is also expressed in the kidney and has been implicated in renal sodium reabsorption and blood pressure regulation. Its expression and activity is strongly linked to a polymorphism (i.e. 6986G > A). Thus, appreciable expression is found in carriers of the CYP3A5*1 (6986A) but not in homozygous carriers of the CYP3A5*3 (6986G) allele. We tested whether the presence of CYP3A5*1 affects blood pressure in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
6
25
1
3
Order By: Relevance
“…Since then, several studies have been performed to investigate the association in different ethnic populations; however, the results have been inconsistent. For example, a large population-based study (n¼6777, age range: 28-75 years) by Kreutz et al 35 showed that the CYP3A5*1 allele was associated with lower SBP only in women. In a study of an elderly Finnish Caucasian population (n¼373, age: X75 years), CYP3A5*1 carriers had a significantly greater hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, several studies have been performed to investigate the association in different ethnic populations; however, the results have been inconsistent. For example, a large population-based study (n¼6777, age range: 28-75 years) by Kreutz et al 35 showed that the CYP3A5*1 allele was associated with lower SBP only in women. In a study of an elderly Finnish Caucasian population (n¼373, age: X75 years), CYP3A5*1 carriers had a significantly greater hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,31,32,[35][36][37][38][39][40] As shown in Figures 2 and 3, there was evidence of heterogeneity between studies (systolic BP (SBP): Figure 4 and Table 3). The stability of these results was also confirmed by sensitivity analysis (data not shown).…”
Section: Characteristics Of the Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…There are a number of conflicting reports regarding the CYP3A genotype influence on cyclosporine pharmacokinetic [27,28]. Therefore, a clear role of this polymorphism on cyclosporine metabolism has not been demonstrated.…”
Section: Cyp3a5 and Abcb1 Genotypes And Cyclosporinementioning
confidence: 99%